2009
DOI: 10.1128/aem.02103-08
|View full text |Cite
|
Sign up to set email alerts
|

NovelCoprinopsis cinereaPolyesterase That Hydrolyzes Cutin and Suberin

Abstract: Three cutinase gene-like genes from the basidiomycete Coprinopsis cinerea (Coprinus cinereus) found with a similarity search were cloned and expressed in Trichoderma reesei under the control of an inducible cbh1 promoter. The selected transformants of all three polyesterase constructs showed activity with p-nitrophenylbutyrate, used as a model substrate. The most promising transformant of the cutinase CC1G_09668.1 gene construct was cultivated in a laboratory fermentor, with a production yield of 1.4 g liter ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…However, considering that the molecular mass of GST is 26 kDa, whereas that of HFB4 is 9 kDa, the actual active concentration of HFB4 is only a fourth of that, theoretically reducing the A 50 concentrations to 8 to 30 mg/ liter. This concentration is comparable to that reported by previous studies to stimulate cutinase hydrolysis of cutin and suberin by HFB2 from T. reesei (24). However, the extent of stimulation of PET hydrolysis by HFB4 was higher (2.5-fold versus 1.4-to 1.7-fold).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, considering that the molecular mass of GST is 26 kDa, whereas that of HFB4 is 9 kDa, the actual active concentration of HFB4 is only a fourth of that, theoretically reducing the A 50 concentrations to 8 to 30 mg/ liter. This concentration is comparable to that reported by previous studies to stimulate cutinase hydrolysis of cutin and suberin by HFB2 from T. reesei (24). However, the extent of stimulation of PET hydrolysis by HFB4 was higher (2.5-fold versus 1.4-to 1.7-fold).…”
Section: Discussionsupporting
confidence: 63%
“…It is tempting to speculate that the expanded arsenal of hydrophobins may be involved in this property. In fact, hydrolysis of the natural polyesters cutin and suberin by a Coprinopsis cinerea polyesterase was enhanced in the presence of T. reesei HFB2 (24).…”
mentioning
confidence: 98%
“…In contrast, Acut1-6hp and Acut2-6hp had higher activity with the C 6 ester pNP-caproate; however, in the case of triacylglycerides, the result for Acut1-6hp and Acut2-6hp was similar to that for Acut3-6hp and FsCut-6hp. Several known cutinases, for example, TtCutA from Thielavia terrestris (5) and PaE from Pseudozyma antarctica (6), have the same substrate profile, but there are also other cutinases or cutinase-like enzymes which have slightly different affinities, with higher levels of activity toward pNP-acetate being detected (25,45,46). Martinez et al (47) suggested that the low levels of activity of cutinases toward pNP esters of long-chain fatty acids are related to the lack of a large hydrophobic area around the active site, which is present in lipases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large volumes of suberin containing materials are available as the by-products of cork, saw-mill, paper and pulp industries (Gandini et al 2006;Kolattukudy 2001). It has therefore been suggested that these materials could be fractionated, and the isolated cutin and suberin could be used for the production of commercially valuable materials and compounds (Kolattukudy 2001;Kontkanen et al 2009). …”
Section: Isolation Of Polyfunctional Fatty Acids From Biomassmentioning
confidence: 98%